New cabinet will lead BN into GEM - Lai, Adrian (New Straits Times, 2016)
THE unveiling of the new cabinet lineup marks an important first step by Prime Minister Datuk Seri Najib Razak in charting Barisan Nasional's course towards the 14th General Election.